Assessment of microplastic abundance and characteristics in the coastal water of Hai Phong, Vietnam - Duong, Thanh Nghi; Nguyen, Dac Ve; Le, Van Nam; Dinh, Hai Ngoc (Vietnam Journal of Marine Science and Technology, 2025)
Microplastics (MPs) in marine environments are currently a source of concern worldwide because they are pollutants to marine organisms and ecosystems. Research on the distribution and characteristics of microplastics can help identify pollution levels or their effects on marine species. In this study, we collected samples from the coastal water of Hai Phong, one of northern Vietnam’s most densely populated areas with several industrial, tourism, and aquaculture zones. The concentration of microplastics in the net was 11.1 ± 7.5 items/m3, and in the bucket was 1,515.4 ± 1,406.4 items/m3; of the 2,659 microplastics (items), 1,041 were fragments, and 1,618 were fibers, accounting for more than 60% of the total. Microplastics are primarily disseminated type fibers with a size of 2 mm, and most of which are made of polyethylene, polypropylene, and polystyrene. The results will serve as a basis for future research into microplastic features and their effects on the sedimentary environment and species in coastal areas of Hai Phong, Vietnam.